La revalorizacion de la tradicion a causa del desencanto con la modernidad - Mansilla, H. C. F. (Nómadas. Critical Journal of Social and Juridical Sciences, 2007)
The elimination of premodern institutions and values has been generally considered as unavoidable and therefore as positive for the purposes of accelerating the historical evolution of any society and of bringing material progress. The traditional order has been supposed to be something basically negative. Modernization embraces, however, destructive factors, which now are increasingly perceived in a more realistic manner. Some premodern aspects deserve a better destiny in collective conscience. Examples of that are religion (as a source of sense and comfort), the classical conception of art and literature (an aesthetics based on beauty) and non-quantitative values.